A techno-economic framework for comparing conventionally and additively manufactured parts for geothermal applications. (December 2021) - Price, Christopher; Armstrong, Kristina; Polsky, Yarom; Wang, Annie; Nimbalkar, Sachin; Chesser, Phillip; Post, Brian; Su, Jiann-Cherng
Abstract: Geothermal reservoir characterization, construction, and operations are technology-intensive activities that contribute significantly to the cost of delivering renewable electricity. The technologies involved, such as downhole tools and drilling equipment, are similar to those used in oil and gas exploration and production must often be adapted for use in the corrosive, high-temperature geothermal reservoir environment. Low production volume of geothermal tools presents a major challenge in meeting the industry's technology needs. Production of specialized tools for geothermal subsurface applications is often cost-prohibitive. Reduced inventory of subsurface well construction, characterization, and production tools causes geothermal reservoir development efficiency and sophistication to lag behind that of the oil and gas industry. Advances in additive manufacturing provide opportunities to advance geothermal technology while reducing lead time and costs associated with production of low-volume, complex parts. This paper performs an initial techno-economic analysis comparing the cost of conventional production techniques and additive manufacturing for geothermal downhole applications. An analysis of representative downhole tools is used to create a framework for estimating fabrication costs of subtractive and additive techniques, including post-print machining required to meet final tolerances. The framework is used to explore several manufacturing scenarios and identify the dominant factors driving manufacturing time and cost. The current feasibility of additive manufacturing for geothermal downhole tool applications is assessed and issues for future development to better meet the needs of the geothermal industry are identified. Highlights: Additive manufacturing has the potential to reduce costs and lead time for geothermal well development and maintenance. Tolerances required for downhole tools require significant post–additive manufacturing build machining. Reducing required post-print machining can make additive manufacturing economically feasibility for geothermal development.